Positional changes in the uvula tip after adenotonsillectomy in children: preliminary result - Chang, Suk Won; Song, Chan Il; Kim, Jeong Hong; Lim, Gil-Chai; Kang, Ju Wan (PeerJ, 2021)
Background Adenotonsillectomy has become the primary treatment for children with sleep-disordered breathing or obstructive sleep apnea. However, few studies have investigated positional changes in the soft palate or uvula after adenotonsillectomy in children. The present study aimed to evaluate positional changes in the uvula tip using cephalometric analyses after adenotonsillectomy in children. Methods We analyzed 160 pediatric patients from December 2015 to July 2016, with 94 pediatric patients who underwent adenotonsillectomy as the experimental group and 66 children who were treated and followed up with frequent tonsillitis as the control group. Positional changes in the uvula tip after surgery in the adenotonsillectomy group were investigated using lateral cephalograms obtained within 1 month before surgery and 3–4 months after surgery. Two lateral cephalogram intervals for a few months in the control group who did not undergo adenotonsillectomy were analyzed. Results The palatal length (23.92 ± 3.47 vs. 24.46 ± 3.26; p = 0.032), palatal angle (43.13 ± 7.76 vs. 46.12 ± 5.91; p < 0.001), and retrouvula length (15.60 ± 3.51 vs. 16.60 ± 2.97; p = 0.009) were significantly increased on postoperative images relative to those on preoperative images. In the control group, there was a significant change in the palatal angle (2.99 ± 5.85 vs. 0.27 ± 4.14; p < 0.001) and retrouvula length (0.99 ± 3.64 vs. 0.05 ± 1.44; p = 0.025), but not in the palatal length (0.58 ± 2.38 vs. 0.043 ± 1.26; p = 0.065). Conclusion The findings of the present study suggest that the uvula tip is displaced in the anteroinferior direction 3 or 4 months after adenotonsillectomy in children. Thus, clinicians should be aware that the retropalatal space may expand after adenotonsillectomy in the pediatric population.
Keywords: Uvula; Children; Adenotonsillectomy; Soft palate